2020
DOI: 10.1002/mp.13963
|View full text |Cite
|
Sign up to set email alerts
|

Visual enhancement of Cone‐beam CT by use of CycleGAN

Abstract: Purpose Cone‐beam computed tomography (CBCT) offers advantages over conventional fan‐beam CT in that it requires a shorter time and less exposure to obtain images. However, CBCT images suffer from low soft‐tissue contrast, noise, and artifacts compared to conventional fan‐beam CT images. Therefore, it is essential to improve the image quality of CBCT. Methods In this paper, we propose a synthetic approach to translate CBCT images with deep neural networks. Our method requires only unpaired and unaligned CBCT i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 37 publications
(69 reference statements)
1
114
2
Order By: Relevance
“…Related cycle-GAN-based sCT studies reported similar values for the ME/MAE of the total body contour with − 3/ 16.1HU [21] and − 6/87HU [33]. The analysis of Kida et al [30] which compared cycle-GAN generated sCT to deformed CT yielded mean HU values for the prostate and bladder of 19HU and 4HU. However, a direct comparison remains difficult since all referenced studies differed from the presented work with regard to the size of the patient collective, the manufacturer-specific image acquisition parameters, the detailed architecture of the GAN and the training of the body site-specific models.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Related cycle-GAN-based sCT studies reported similar values for the ME/MAE of the total body contour with − 3/ 16.1HU [21] and − 6/87HU [33]. The analysis of Kida et al [30] which compared cycle-GAN generated sCT to deformed CT yielded mean HU values for the prostate and bladder of 19HU and 4HU. However, a direct comparison remains difficult since all referenced studies differed from the presented work with regard to the size of the patient collective, the manufacturer-specific image acquisition parameters, the detailed architecture of the GAN and the training of the body site-specific models.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding target volume dose metrics, two related studies reported dosimetric differences between the sCT and CT with a comparable accuracy to our study. A V 95 of 0.2-0.7% for the H&N body site [35] and an absolute difference of D 98 , D 50 and D 2 of − 1 to 0 Gy for the pelvic body site [30] were obtained, respectively. For the thoracic body region, D 98 showed the largest deviations and for the D 50 and D 2 outliers were observed which can be attributed to remaining uncertainties due to the breathing pattern.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies using DL for pCT generation from CBCT are scarce for brain, 55 H&N, [13][14][15] pancreas, 38 or prostate cancer. [35][36][37]55,56 The studies involved an imaging analysis (pCT vs. reference CT), but only half of them evaluated the dose accuracy. Among the three H&N studies using DL for pCT generation from CBCT, [13][14][15] one involved training a U-Net neural network on 50 coregistered CBCT/CT images and performing a test based on data from 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, pCT generated from CBCT are used to monitor delivered doses or to estimate the cumulative delivered dose during the treatment course in the context of dose‐guided adaptive radiotherapy. Studies using DL for pCT generation from CBCT are scarce for brain, 55 H&N, 13–15 pancreas, 38 or prostate cancer 35–37,55,56 . The studies involved an imaging analysis (pCT vs. reference CT), but only half of them evaluated the dose accuracy.…”
Section: Discussionmentioning
confidence: 99%